Use of Jianpi Jiedu Herbs in Patients with Advanced Colorectal Cancer: A Systematic Review and Meta-Analysis. (29th January 2018) - Zhang, Shaofan; Shi, Li; Mao, Dan; Peng, Weijun; Sheng, Chenxia; Ding, Chenchen; Lin, Fengxia; Lei, Caiyun; Zhang, Sifang
Abstract : Objective . To systematically review the effect of invigorating Pi and detoxification (Jianpi Jiedu, (JPJD)) herbs in advanced colorectal cancer (CRC) patients receiving chemotherapy. Methods . Three English and four Chinese databases were searched. Literature was screened by EndNote X7 and data were analyzed by RevMan 5.2. Results . This review comprised 12 randomized clinical studies of 701 patients. The results showed that JPJD herbs improved the therapeutic effect on Chinese medicine symptoms [risk ratio (RR) = 1.59; 95% confidence interval (CI): 1.35 1.88] and Karnofsky performance score [RR = 2.07; 95% CI: 1.52 2.82] for advanced CRC patients receiving chemotherapy, lowered the Chinese medicine symptoms' score [weighted mean difference = −2.44; 95% CI: −3.23 −1.64], reduced the incidence of nausea and vomiting [RR = 0.23; 95% CI: 0.11 0.49], improved platelet at toxicity grades III-IV [odds ratio = 0.29; 95% CI: 0.12 0.74] and I–IV [RR = 0.65; 95% CI: 0.51 0.82], and improved white blood cell at toxicity grades III-IV [RR = 0.37; 95% CI: 0.23 0.58] and I–IV [RR = 0.69; 95% CI: 0.60 0.79]. However, the results showed no significant effect on tumor response. Conclusion . JPJD herbs can improve quality of life, relieve symptoms, and reduce adverse events of advanced CRC patients receiving chemotherapy.